Forest fuel inventory in Acacia mangium and Hevea brasiliensis at Ulu Sedili Forest Plantation, Kota Tinggi, Johor - Idris, Insan Nurkamil (2018)
Forest plantation has become increasingly important where it could provide wood supply and many services. However, every forest plantation is risked to forest fire which could decrease the wood production and damage the environment. Forest fire management plan needs to be established in the plantation to reduce the risk of forest fire. Before the plan could be established, the fuel components of the particular plantation need to be characterised. Acacia mangium and Hevea brasiliensis species are fast growing species that have currently been planted in the forest plantations in Malaysia. The aim of the study was to characterise the forest fuel components that are available in the Acacia mangium and Hevea brasiliensis stands and compare the fuel loading between these two stands. This study was conducted at Hulu Sedili Forest Plantation. Six fuel components were measured: downed woody material, litter, duff depth, herbaceous, shrubs and small trees (< 3m height). The result showed that A. mangium stand had higher quantity and density of fuels compared to H. brasiliensis stand. The result of t-test analysis showed that Acacia mangium stand had significantly higher fuel loading compared to Hevea brasiliensis stand. This difference occurred due to the physiological characteristics of the stand species and silviculture treatment of the site. Forest plantation managers need to take precaution to reduce or avoid forest fire from happening by reducing the fuel in the hazardous area and also monitored frequently around the plantation area.